Genome-Wide Identification and Functional Prediction of Long Non-coding RNAs Involved in the Heat Stress Response in Metarhizium robertsii - Wang, Zhangxun; Jiang, Yuanyuan; Wu, Hao; Xie, Xiangyun; Huang, Bo (Frontiers in Microbiology, 2019)
Long noncoding RNAs (lncRNAs) play a significant role in stress responses. To date, only a few studies have reported the role of lncRNAs in insect-pathogenic fungi. Here, we report a genome-wide transcriptional analysis of lncRNAs produced in response to heat stress in Metarhizium robertsii, a model insect-pathogenic fungus, using strand-specific RNA sequencing. A total of 1655 lncRNAs with 1742 isoforms were identified, of which 1081 differentially expressed (DE) lncRNAs were characterized as being heat responsive. By characterizing their genomic structures and expression patterns, we found that the lncRNAs possessed shorter transcripts, fewer exons, and lower expression levels than the protein-coding genes in M. robertsii. Furthermore, target prediction analysis of the lncRNAs revealed thousands of potential DE lncRNA–messenger RNA (mRNA) pairs, among which 5381 pairs function in the cis-regulatory mode. Further pathway enrichment analysis of the corresponding cis-regulated target genes showed that the targets were significantly enriched in the following biological pathways: the Hippo signaling pathway and cell cycle. This finding suggested that these DE lncRNAs control the expression of their corresponding neighboring genes primarily through environmental information processing and cellular processes. Moreover, only 26 trans-regulated lncRNA–mRNA pairs were determined. In addition, among the targets of heat-responsive lncRNAs, two classic genes that may be involved in the response to heat stress were also identified, including hsp70 (XM_007821830 and XM_007825705). These findings expand our knowledge of lncRNAs as important regulators of the response to heat stress in filamentous fungi, including M. robertsii.